THE INFLUENCE OF MOBILE MARKETING, E-SERVICE QUALITY, AND COST ON CUSTOMER SATISFACTION AMONG DANA APPLICATION USERS - Ikramuddin; Aini Liza; Sapna Biby; Nurainun (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of mobile marketing, e-service quality, and cost on customer satisfaction among DANA application users, specifically students of the Faculty of Economics and Business at Malikussaleh University. A quantitative method was used through a survey of 114 respondents. Multiple linear regression analysis revealed that all three independent variables have a positive and significant effect on customer satisfaction. Mobile marketing and cost have the strongest influence, followed by e-service quality. These findings suggest that enhancing mobile marketing strategies, service quality, and cost efficiency can improve customer satisfaction with the DANA application. The results provide valuable insights for DANA managers to improve digital service quality.